Pengaruh Pembiayaan Konsumtif, Pembiayaan Modal Kerja dan Fee-Based Income Terhadap Profitabilitas BPRS BDW Yogyakarta - Mufti Alam Adha; Wahyuni Liya Kusumawardhani (FEB Universitas Sultan Ageng Tirtayasa, 2022)
The level of financing and fee-based income at the BPRS indicates the level of quality of the bank. If a bank wants to improve its performance and quality, one way to improve it is to look for sources of income outside the primary income. However, increased financing and fee-based income does not always increase profitability. The researcher investigated whether murabahah, ijarah, mudharabah, and fee-based income financing have an effect on profitability and what is the cause of the imbalance between the increase in funding and fee-based income with profitability, especially ROA and ROE. This study uses a quantitative approach. The object of the research is PT BPRS Bangun Drajat Warga Yogyakarta. Murabahah, ijarah, mudharabah, and fee-based income financing as independent variables and profitability is the dependent variable. The data analysis technique used in this research is multiple linear regression. In addition, multiple regression tests showed that simultaneously the independent variables did not have a significant effect on ROA. Then simultaneously, the independent variables have a significant effect on ROE. Partially, murabahah, ijarah, mudharabah, and fee-based income financing have no significant impact on ROA. Then the funding of murabahah, ijarah, mudharabah, and fee-based income has no significant effect on ROE.Keywords: financing, fee-based income, profitability, BPRS